Improvement Differential fault attack on TWINE - Yang GAO; Yong-juan WANG; Lei WANG; Tao WANG (Tongxin xuebao)
A new method of differential fault attack was proposed,which was based on the nibble-group differential diffusion property of the lightweight block cipher TWINE.On the basis of the statistical regularity of the S-box differential distribution,the lower bound of the probability of recovering round key was calculated.Then expectation of number of fault injections when restoring seed key can be estimated.Theoretical proof and experimental results both show that an average of nine times of fault injections in 33,34 and 35 rounds bring about the seed key recovered completely.Finally,the improvement of the fault injection location was proposed,which enhances the feasibility of the genuine attack.